Shifting ground: exploring the backdrop to translating and interpreting. (3rd April 2017) - Rock, Frances
ABSTRACT: Previous scholarship has assumed a monolingual norm. This norm has been noted across disciplines and societies, where it demands assimilation and language shift. However, socially responsible language scholars have increasingly rejected this norm in favour of renewed interest in language contact, and associated complexity. Many social institutions in which interpreters and translators work in modernist nation states view languages as separate, separable units which come into contact in highly regularised ways and can therefore be highly regulated. I argue instead that a renewed focus on ethics in the study and practice of translation and interpreting involves recognising forms of communication which are increasingly common and diversified due to superdiversity. This paper describes an investigation into multilingual language practices in four changing UK cities, using Linguistic Ethnography. The study's own approach to ethical practice is first evaluated. I then ask how increased study of multilingualism can contribute to interpreters' and translators' work and how this work fits with contemporary patterns of language use, drawing on distinctions between the ethical and moral. I suggest that, whilst translating and interpreting can offer an ethicised approach to language contact, a truly moral approach may require rich understands of contemporary superdiverse societies.